ASSESSMENT AND SELF-ASSESSMENT OF PRIMARY SCHOOL PUPILS IN THE FIELD OF TECHNICAL EDUCATION IN THE GENDER CONTEXT - CASTKOVA, Pavlina; PROVAZKOVA STOLINSKA, Dominika (Trends in education, 2016)
The article deals with the assessment of pupils at primary school in the context of technical education. These processes are seen as important for the development of personal qualities and the process of socialization of the child, which is declared by Framework Educational Program for Basic Education. The main aim of this paper is to present the possible gender differences in evaluation and self-assessment of primary school pupils as one aspect, which affect the development of future professional orientation. Because of the whole society strengthening efforts to revive the technical disciplines this issue is addressed in the context of teaching technical subjects at primary school (the practical work). This article contains the presentation of the planned research; the results of it might serve to identify the possible differences in the process of selfassessment of pupils. Given that the evaluation of teachers is one of the key factors affecting the pupil´s self- assessment, one of the objectives of the research is to identify the possible differences in evaluation strategies by teachers with regard to the gender of pupils, character self-assessment activities controlled by teacher and the specifics of evaluation in technical education at primary school.
Keywords: gender; assessment; pupil´s self-assessment; primary school; technical education